Fusobacterium nucleatum induces a tumor microenvironment with diminished adaptive immunity against colorectal cancers - Kim, Han Sang; Kim, Chang Gon; Kim, Won Kyu; Kim, Kyung-A; Yoo, Jinseon; Min, Byung Soh; Paik, Soonmyung; Shin, Sang Joon; Lee, Hyukmin; Lee, Kyungwon; Kim, Hoguen; Shin, Eui-Cheol; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background & Aims: Fusobacterium nucleatum (FN) plays a pivotal role in the development and progression of colorectal cancer by modulating antitumor immune responses. However, the impact of FN on immune regulation in the tumor microenvironment has not been fully elucidated. Methods: The abundance of FN was measured in 99 stage III CRC tumor tissues using quantitative polymerase chain reaction. Gene expression profiles were assessed and annotated using consensus molecular subtypes (CMS), Gene Ontology (GO) analysis, and deconvolution of individual immune cell types in the context of FN abundance. Immune profiling for tumor infiltrating T cells isolated from human tumor tissues was analyzed using flow cytometry. Ex vivo tumor-infiltrating T cells were stimulated in the presence or absence of FN to determine the direct effects of FN on immune cell phenotypes. Results: Gene expression profiles, CMS composition, abundance of immune cell subtypes, and survival outcomes differed depending on FN infection. We found that FN infection was associated with poorer disease-free survival and overall survival in stage III CRC patients. FN infection was associated with T cell depletion and enrichment of exhausted CD8+ and FoxP3+ regulatory T cells in the tumor microenvironment. The presence of FN in tumors was correlated with a suppressive tumor microenvironment in a T cell-dependent manner. Conclusion: FN enhanced the suppressive immune microenvironment with high depletion of CD8+ T cells and enrichment of FoxP3+ regulatory T cells in human colorectal cancer cases. Our findings suggest a potential association for FN in adaptive immunity, with biological and prognostic implications.